The Effect of Transformational Leadership and Work Environment on Organizational Productivity with Employee Performance as the Mediating Variable - Subroto, Setyowati; Wahdiniawati, Siti Annisa; Nampira, Ardi Azhar; Rejeki, Marsudi Endang Sri; Syamsulbahri, Syamsulbahri (Westscience Press, 2025)
This study investigates the influence of transformational leadership and work environment on organizational productivity, with employee performance serving as a mediating variable among Indonesian MSME workers. Using a quantitative approach with 170 samples and data analyzed via Structural Equation Modeling-Partial Least Squares (SEM-PLS), the findings reveal significant direct and indirect relationships. Transformational leadership and work environment positively impact employee performance, which in turn significantly enhances organizational productivity. Employee performance is confirmed as a critical mediating factor, emphasizing the importance of leadership and conducive work environments in achieving optimal productivity. The study provides valuable insights for MSME leaders to strategically invest in human capital and organizational culture to foster growth and competitiveness.